THE USE OF THE STOCHASTIC FRONTIER METHOD FOR MEASURING THE PERFORMANCE OF RICE FARMING IN THE FRONTIER, REMOTE, AND UNDERDEVELOPED AREAS IN MERAUKE REGENCY, SOUTH PAPUA PROVINCE, INDONESIA - Widyantari, Ineke Nursih; Loppies, Stanly HD; Maulany, Gerzon; Wiranto, Retnowati (Agric, 2023)
Merauke is one of the regencies in South Papua Province with flatland areas, making it very suitable for agriculture. In 2011, Merauke Regency was declared a food barn for Eastern Indonesia by President Jokowi. Tanah Miring District is one of the rice centers in Merauke. One of the villages in Tanah Miring District is Sumber Harapan Village. This study aims to examine (1) factors that influence the production of rice farming in Sumber Harapan Village, Merauke Regency; (2) factors that influence the technical efficiency of rice farming in Sumber Harapan Village, Merauke Regency; and (3) the level of technical efficiency of rice farming in Sumber Harapan Village, Merauke Regency. This research was conducted in Sumber Harapan Village, Tanah Miring District, Merauke Regency, from June to August 2022. The data used were primary data and secondary data. Primary data were obtained from interviews, questionnaires, and observations. Meanwhile, the secondary data were obtained from Statistics Indonesia (BPS) and other literature. The number of samples used was 50 rice farmers. The results showed that the factors influencing the production of rice farming in Sumber Harapan Village, Merauke Regency, were machines, labor, and land area. Meanwhile, the factors influencing the technical efficiency of farming production in Sumber Harapan Village, Merauke Regency were a family burden, education, land status, and membership in farmer groups. The average level of technical efficiency of rice farming in Sumber Harapan Village, Merauke Regency, was 0.97, which is said to be inefficient since it is below one.